2021
DOI: 10.3390/ani11051348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Backfat Thickness and the Interval from Altrenogest Withdrawal to Estrus on Reproductive Performance of Gilts

Abstract: Estrus synchronization of gilts can be achieved by feeding the orally active progestogen altrenogest (AT) to cycling gilts at 20 mg/day for 14 to 18 days with gilts usually returning to estrus 4 to 8 days after the last feeding. In practice, gilts failing to exhibit estrus by 6 days after AT withdrawal may compromise weekly breeding targets. The cause of prolonged intervals to estrus are unknown but may involve prolonged suppression due to the release of progesterone (P4), and by extension AT, from adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…The results of this study showed that 9% and 14% more sows in the Large and Medium groups compared with the Small group were in estrus within 8 days after synchronization treatment. These results do not agree with those reported by Thitachot et al [ 32 ], who observed longer intervals to estrus in heavier gilts. They explained that the relationship may have been due to a larger reservoir of Altrenogest in the adipose tissue in fatter gilts.…”
Section: Discussioncontrasting
confidence: 98%
“…The results of this study showed that 9% and 14% more sows in the Large and Medium groups compared with the Small group were in estrus within 8 days after synchronization treatment. These results do not agree with those reported by Thitachot et al [ 32 ], who observed longer intervals to estrus in heavier gilts. They explained that the relationship may have been due to a larger reservoir of Altrenogest in the adipose tissue in fatter gilts.…”
Section: Discussioncontrasting
confidence: 98%
“…As an ideal experimental animal model, pigs are widely used in metabolic disease studies of obesity and diabetes [ 3 , 50 ]. However, the fat content of pigs has also been studied as an important economic trait in animal husbandry [ 51 ], and its fat deposition ability will affect pig carcass quality, lean meat rate, and reproductive performance [ 52 , 53 , 54 ]. Therefore, subcutaneous fat thickness is a key indicator for assessing fat deposition in pigs and the reproductive performance of sows, and is regarded as a significant trait in pig breeding.…”
Section: Discussionmentioning
confidence: 99%